1999
DOI: 10.1901/jaba.1999.32-247
|View full text |Cite
|
Sign up to set email alerts
|

Functional Communication Training Using Assistive Devices: Recruiting Natural Communities of Reinforcement

Abstract: We evaluated the effectiveness of functional communication training (FCT) as an intervention for the problem behavior exhibited by 5 students with severe disabilities both in school and in the community. Following an assessment of the function of their problem behavior, the students were taught to use assistive communication devices in school to request the objects and activities that presumably were maintaining their behavior. Multiple baseline data collected across the students indicated that not only did th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(99 citation statements)
references
References 35 publications
(43 reference statements)
7
88
1
3
Order By: Relevance
“…In addition to the improvements in children's challenging behavior, a few studies (i.e., Moes & Frea, 2000Symon, 2005) reported concomitant positive outcomes that showed that children's communicative skills increased during or after parent-implemented intervention phases. This supported assumptions on the communicative function of challenging behavior of children with disabilities (Durand, 1999). In other words, the acquisition of appropriate communication skills by children seemed to help reduce challenging behavior.…”
Section: Treatment Integrity Of Parent-implemented Interventionssupporting
confidence: 64%
“…In addition to the improvements in children's challenging behavior, a few studies (i.e., Moes & Frea, 2000Symon, 2005) reported concomitant positive outcomes that showed that children's communicative skills increased during or after parent-implemented intervention phases. This supported assumptions on the communicative function of challenging behavior of children with disabilities (Durand, 1999). In other words, the acquisition of appropriate communication skills by children seemed to help reduce challenging behavior.…”
Section: Treatment Integrity Of Parent-implemented Interventionssupporting
confidence: 64%
“…Our review of 76 studies on FCT published between 1985 and 2009 revealed that only 19 studies (29%) included a description of a schedule thinning phase. In some studies, schedule thinning was not necessary because participants did not use the alternative communication response excessively or inappropriately (e.g., Durand, 1999); however, most studies that did not include schedule thinning did not comment on this issue. Of the 19 studies that included schedule thinning, a total of 52 applications 1 of FCT with schedule thinning were described.…”
Section: Schedule Thinning Proceduresmentioning
confidence: 99%
“…This finding was most likely related to the fact that the community-based listeners were not sign literate, but they were able to interpret the persons' picture-based communications. In a later study, Durand (1999) found that unfamiliar listeners responded appropriately (without training) to the SGD-based communication initiations of five students with developmental disabilities. While these findings suggest that both low-and high-tech assistive communication technologies may be effective in community setting with unfamiliar listeners, there are relatively few studies into this important clinical issue, especially regarding the use of CBI and the newer generation of iPad-based SGDs.…”
Section: Clinical Applicationmentioning
confidence: 88%